Does Physical Activity Improve Inhibition in Kindergarteners? A Pilot Study. Issue 4 (August 2022) - Giordano, Giulia; Alesi, Marianna
Substantial empirical evidence supports the positive effects of physical activity (PA) on executive functions, but not all forms of physical activity benefit equally. Among kindergarteners, cognitively-engaging exercise seems to more strongly effect EF than simple exercise. We aimed to investigate several qualitatively different exercise formats on kindergarteners' inhibition. Participants were 75 children (M age = 68.1 months), recruited from 14 classrooms of three kindergarten schools. They were randomly assigned to three groups: control group, free play group (non-cognitively-engaging PA), and an intervention group (cognitively-engaging PA). The intervention group performed 18 sessions of a cognitively engaging PA (tasks requiring movements and inhibitory behavior skills). We assessed "hot" and "cool" aspects of inhibition using the Day-Night Stroop test, Head-Shoulders-Knees-Toes, Gift Wrap, and Snack Delay. We found that the intervention group obtained a more consistent performance improvement on post-test measures of hot and cool inhibition than did the free play group.